The Effect of Managerial Ownership, Profitability and Social Responsibility on Tax Avoidance in Retail Trade Sub-Sector Companies Listed on the Indonesia Stock Exchange - Jessica (Outline Publisher, 2022)
This study aims to determine whether Managerial Ownership, Profitability and Social Responsibility have a significant effect on Tax Avoidance in retail trade sub sector companies that are listed on the Indonesia Stock Exchange. The population in this study are retail trade sub-sector companies listed on the Indonesia Stock Exchange were 26 companies. The research sample were 7 companies with purposive sampling technique. The results showed managerial ownership and Profitability variable did not affect Tax Avoidance in retail trade sub sector companies listed on the Indonesia Stock Exchange while Corporate Social Responsibility affected Tax Avoidance in retail trade sub sector companies that are listed on the Indonesia Stock Exchange. F test results show that the Managerial Ownership, Profitability and Corporate Social Responsibility variables affect Tax Avoidance in retail trade sub sector companies listed on the Indonesia Stock Exchange. The results of the coefficient of determination test show that the Tax Avoidance variable can be explained by the variables of Managerial Ownership, Profitability and Corporate Social Responsibility, while the remaining Tax Avoidance variables can be explained by other variables not examined in this study such as Leverage, Company Size and Audit Committees.